2007
DOI: 10.1093/pcp/pcm140
|View full text |Cite
|
Sign up to set email alerts
|

NtPolI-like1 and NtPolI-like2, Bacterial DNA Polymerase I Homologs Isolated from BY-2 Cultured Tobacco Cells, Encode DNA Polymerases Engaged in DNA Replication in Both Plastids and Mitochondria

Abstract: Two cDNAs encoding homologs of bacterial DNA polymerase I were isolated from cultured tobacco (Nicotiana tabacum) BY-2 cells, and the corresponding genes were named NtPolI-like1 and NtPolI-like2. High sequence similarity suggested that they are orthologous genes each derived from respective parental species of N. tabacum, an allotetraploid plant. Each of the NtPolI-like1/2 gene products had a putative transit peptide for plastid localization at the N-terminus, followed by a 3'-5' exonuclease domain in the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
60
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 36 publications
3
60
0
Order By: Relevance
“…This is largely due to our ignorance concerning some of the most basic factors, such as DNA polymerases, that contribute to this fundamental process in plants. Many studies have suggested that the PolI-like DNA polymerases found in higher plants are responsible for most if not all the DNA-synthesis activity found in mitochondria and plastids (Kimura et al, 2002;Mori et al, 2005;Ono et al, 2007). This is based on the biochemical properties of the recombinant proteins, which indicate that these enzymes have sufficient processivity to be able to replicate both genomes.…”
Section: Discussion An Essential Role For the Poli Genes In Higher Plmentioning
confidence: 99%
See 4 more Smart Citations
“…This is largely due to our ignorance concerning some of the most basic factors, such as DNA polymerases, that contribute to this fundamental process in plants. Many studies have suggested that the PolI-like DNA polymerases found in higher plants are responsible for most if not all the DNA-synthesis activity found in mitochondria and plastids (Kimura et al, 2002;Mori et al, 2005;Ono et al, 2007). This is based on the biochemical properties of the recombinant proteins, which indicate that these enzymes have sufficient processivity to be able to replicate both genomes.…”
Section: Discussion An Essential Role For the Poli Genes In Higher Plmentioning
confidence: 99%
“…In addition, the measured in vitro characteristics of these enzymes correspond almost perfectly to those measured ex vivo from the purified DNA-synthesis activity of mitochondria and plastids (Spencer and Whitfeld, 1969;Sala et al, 1980;McKown and Tewari, 1984;Heinhorst et al, 1990;Meissner et al, 1993). All these elements, plus the fact that they are present in both organelles (Elo et al, 2003;Christensen et al, 2005;Mori et al, 2005;Ono et al, 2007;Wamboldt et al, 2009), suggest that the PolI DNA polymerases are responsible for DNA replication in plant organelles.…”
Section: Discussion An Essential Role For the Poli Genes In Higher Plmentioning
confidence: 99%
See 3 more Smart Citations